Pseudohypokalaemia and pseudohypoxaemia in a patient with acute myeloid leukaemia - Chothia, Mogamat-Yazied; Davids, Mogamat Razeen (African Journal of Nephrology, 2020)
Spurious laboratory results are frequently encountered in patients with haematological disorders and lead to unnecessary additional laboratory investigations and inappropriate treatment. An 80-year-old woman, known with acute myeloid leukaemia, was admitted with suspected sepsis. Laboratory tests revealed a leukocyte count of 358 x 109/L, serum potassium concentration of 2.6 mmol/L and partial pressure of arterial oxygen of 5.3 kPa. The patient did not display any clinical or electrocardiographic features of hypokalaemia and there were no signs of respiratory distress. A diagnosis of pseudohypokalaemia and pseudohypoxaemia was made and inappropriate therapeutic interventions were avoided. Pseudohypokalaemia and pseudohypoxaemia should always be a consideration in patients with hyperleukocytosis due to haematological malignancies, especially when there are no clinical features to support these findings. The inappropriate administration of potassium in such cases may cause serious cardiac arrythmias.